Posłannictwo i zadania dziejowe rodziny. Transkrypcja myśli pedagogicznej Stanisława Wawrzyńca Staszica - Żywczok, Alicja (Biuletyn Historii Wychowania, 2020)
In view of the fact that issues related to the family in the literary works of Stanisław Wawrzyniec Staszic are far less known than his socio-political views or his opinions about education, the author of this paper decided to creatively explore this treasure of Polish culture. The results of this study may significantly enhance the educational resources of sub-disciplines of teaching like familial teaching, the history of upbringing, the theory of upbringing and general teaching. Quoting from Stanisław Staszic, the author provides answers to several research issues, namely how Staszic perceived the family and what tasks (and missions) he assigned to family members, the parents and the offspring; the types of primeval families he identified (using the criterion of the law of nature); the role that he assigned to families with respect to the integration of mankind, the integration of a nation, and Poland regaining independence; the factors which, in his opinion, were the main obstacles to families undertaking historical tasks (including Polish families). In order to define these issues, the author of this paper used hermeneutic methods to interpret the literary output of Stanisław Staszic, revealing in the process the philosopher’s views on the family, its tasks, functions and the roles of its members, with special emphasis placed on the mother, father and the offspring. An analysis of the types of families in the initial phases of the existence of mankind was another effort worth making together with considering the obstacles that families encounter when carrying out their historical tasks